Preferences of recreational activity during leisure among medical students in UPM - Osman, Nur Aida (2019)
University students, particularly medical students have a busy schedule that gives them little time to spend for recreational activities. This study is done to observe the preferences of recreational activity and factors influencing medical students at Universiti Putra Malaysia (UPM) to participate in recreation during leisure. The data were collected using a questionnaire among medical students in UPM. A total of 300 respondents were selected as the sample for this study. All the information from questionnaire has been analysed using SPSS. Results showed that the three highest preferred activities for medical students are playing electronic games (M=4.13), picnic (M=3.94) and jogging or running (M=3.65), while the three lowest mean for preferred activities were fishing (M=2.46), making crafts (M=3.08) and swimming (M=3.14). Results from this study also shows that accessibility (p=0.004), time (p=0.001), physical fitness (p=0.001) and skills (p=-0.019) were significantly correlated with the frequency of participating in recreational activities. This study shows that medical students participate less in recreation, therefore suggestions such as providing a bus frequently to the recreational area, adding sports course or sport slot for ten minutes every morning or evening and provide more skills sports class for those who wants to join it.